FLUCTUATION OF POST-PRANDIAL PLASMA MINERAL LEVEL OF JUVENILE JAPANESE FLOUNDER, Paralichthys olivaceus FED DIETARY PHOSPHORUS AND PHYTASE SUPPLEMENTATION - Asda Laining; Rachmansyah Rachmansyah; Lideman Lideman; Shunsuke Koshio (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
In order to investigate the phytic acid degradation in the gut of post juvenile Japanese flounder, indirect method was carried out by measuring the pre-prandial and postprandial plasma mineral and alkaline phosphatase (ALP) level as well as liver phosphorus content. The experiment was designed into a Randomized Block in which experiment units were grouped according to sampling days at 10, 20 and 30 days of feeding time. Experimental diets contained three levels of dietary inorganic phosphorus at 0.0; 0.25 and 0.5% combined with two levels of dietary phytase at 0 and 2,000 FTU/kg diet. Juvenile Japanese flounder (IBW = 36.2 g) were randomly distributed into 6 tanks of a 200 L capacity with density of 15 fish/tank. Blood sampling was carried out at 0 hour (before feeding or pre-prandial) and at 1, 3, 6 and 12 hour post feeding (post-prandial) time in three sampling days, respectively. Plasma was measured for mineral and ALP levels, while liver was analyzed for P content. The observation showed that fish fed without both dietary IP and phytase supplements had the lowest postprandial plasma IP, Mg and ALP levels during 12-h postprandial period. Plasma IP level at 6-h post-feeding in groups fed dietary 0.25 and 0.5% IP were significant higher when diet supplemented with phytase than those without phytase supplement. Peak level of plasma IP in fish fed 0.25% IP was similar to fish fed 0.5% with the presence of dietary phytase. At 1 and 3-h post-feeding, plasma Ca level increased in all groups, but significant difference was only observed between group fed diet without both dietary IP and phytase and other groups. Similar to plasma IP level, peak of plasma Mg and ALP concentration occurred in fish fed 0.25% IP together with phytase, and did not significantly differ from fish fed with 0.5% IP even when phytase was included in diet.